2020
DOI: 10.1088/1757-899x/991/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of encapsulation agents on antioxidant activity and moisture content of spray dried powder from Mahkota Dewa fruit extract

Abstract: Mahkota Dewa is rich in bioactive compounds including mangiferin, saponin and polyphenols. This work aims to investigate the encapsulation of Mahkota Dewa by spray drying using different types of encapsulation agent. A subcritical water extraction process was used to extract the bioactive compounds from dried Mahkota Dewa prior to spray drying process. The encapsulation agents used were maltodextrin (MT), arabic gum (AG) and mixture of arabic gum-maltodextrin (AG-MT). The spray drying conditions namely inlet d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…• Ácidos grasos (palmítico, oleico, linoleico, esteárico, semilla de uva, pescado) • Fenoles (polifenoles, carotenos, antocianinas, licopeno, curcumina, vainillina, ácido gálico, ácido cumárico, ácido ferúlico) • Probióticos (L. acidophilus spp., L. paracasei spp.) Ballesteros et al, 2017;Böger et al, 2018;Rezvankhah et al, 2019;Leyva-Jiménez et al, 2020;Guo et al, 2020;Neves et al, 2019;Kathiman et al, 2020;Ogrodowska et al, 2020;Santana Aguiar et al, 2020;Navarro-Flores et al, 2020;Pashazadeh et al, 2021;Jovanović et al, 2021;Jordán-Suárez et al, 2021;Xin et al, 2022 Otro ejemplo de encapsulación de aceites esenciales esta reportado por Cáceres et al (2020), quienes usaron un proceso de extrusión en una matriz de alginato en un medio de cloruro de calcio para encapsular aceites esenciales de toronja. Ante la variación de la concentración del cloruro de calcio (2, 5 y 10%) y el tiempo de agitación (30, 45 y 60 min) se notó variación en la eficiencia y rendimiento de proceso.…”
Section: Exunclassified
“…• Ácidos grasos (palmítico, oleico, linoleico, esteárico, semilla de uva, pescado) • Fenoles (polifenoles, carotenos, antocianinas, licopeno, curcumina, vainillina, ácido gálico, ácido cumárico, ácido ferúlico) • Probióticos (L. acidophilus spp., L. paracasei spp.) Ballesteros et al, 2017;Böger et al, 2018;Rezvankhah et al, 2019;Leyva-Jiménez et al, 2020;Guo et al, 2020;Neves et al, 2019;Kathiman et al, 2020;Ogrodowska et al, 2020;Santana Aguiar et al, 2020;Navarro-Flores et al, 2020;Pashazadeh et al, 2021;Jovanović et al, 2021;Jordán-Suárez et al, 2021;Xin et al, 2022 Otro ejemplo de encapsulación de aceites esenciales esta reportado por Cáceres et al (2020), quienes usaron un proceso de extrusión en una matriz de alginato en un medio de cloruro de calcio para encapsular aceites esenciales de toronja. Ante la variación de la concentración del cloruro de calcio (2, 5 y 10%) y el tiempo de agitación (30, 45 y 60 min) se notó variación en la eficiencia y rendimiento de proceso.…”
Section: Exunclassified
“…Maltodextrin can effectively and stably encapsulate naturally occurring active compounds derived from plants, such as honey and cocoa (Jafari et al, 2008;Luna-Guevara et al, 2017). Studies have reported that adding maltodextrin to Mahkota Dewa fruit and pomegranate juice increased their antioxidant capacity and phenolic content compared to other encapsulating agents (Adetoro et al, 2020;Kathiman et al, 2020;). Maltodextrin has also been utilised to protect polyphenols in chokeberry, blackberry powder and acai (Ćujić-Nikolić et al, 2019;Ferrari et al, 2012;Tonon et al, 2010).…”
Section: Antioxidant Capacitymentioning
confidence: 99%